Voices in the Machine: Class, Subjectivity and Desire in Victorian Women’s Factory Poems - Fabienne Moine (Cahiers Victoriens et Edouardiens)
This paper aims to explore how industrial culture shaped the poetical imaginary of Victorian women. We often fail to consider that not all factory poems spring from the minds of middle and upper-class reform-minded authors. The working-class poets produced a limited but significant number of industrial and largely autobiographical poems too. The first objective of this paper is to present the voices of the upper and middle-class women poets, who show sympathy for the labourers as they try to advance the cause of the female workers. In their poems, they denounce the horrendous working conditions in factories and the mechanistic dehumanization of workers. I wish then to confront these voices with the ones of the working-class women poets who depict a different image of the factory girls: they were concerned with the conservative values of the family and the nation that factory girls could convey, in spite of their degraded condition. The absence of work and factories in their poems is compensated for by the representations of the productive and reproductive potential of these factory girls and by those of matrimonial and patriotic desire. Finally, ‘factory girls’, who write autobiographical poems and construct their subjectivity as real insiders, produce factory poems that give prestige and dignity to manual work and that develop their pride, their working-class consciousness and their sense of communal solidarity. If they often copy bourgeois poems by adopting middle-class subjectivity and sentimentalism useful to gain respectability and visibility, they also try to resist the bourgeois poetical codes by writing their own kind of factory poems. The confrontation of these poetic voices shows that there is no clear-cut and unique response to industrialization and mechanization among Victorian women poets.